NUT Carcinoma Without Upfront Surgical Resection: A Case Report. Issue 5 (16th July 2021) - Leeman, Rachel; Pinkney, Kerice; Bradley, Julie A.; Ruiz, Robert; DuBois, Steven G.; French, Christopher; Trucco, Matteo
Abstract : Nuclear protein in testis carcinoma is a rare and highly aggressive carcinoma associated with a 70% mortality rate 1 year from diagnosis and a median survival of only 6.5 months. No established treatment protocol exists, although some success has been achieved using a multimodal approach including early surgical resection and adjuvant chemotherapy and radiation. Prior studies have not demonstrated successful treatment in the absence of upfront surgical resection. We describe the first reported case of a patient with unresectable nuclear protein in testis carcinoma treated successfully with definitive chemotherapy using the Scandinavian Sarcoma Group IX Protocol and concurrent radiation therapy, but without surgical resection.